Theoretical aspects of financial sanction - Устинова, Ірина Петрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
This article deals with the analysis of theoretical background of the notion in the sphere of both financial and law responsibility and its structural element - the financial and law sanction. The author researches the real scientific ideas as to the notions "financial and law sanction", "fine". The author also analyses the functions of financial and law sanctions including as the basement of common law theory so as financial law in particular. His special task is to analyses the most characteristic determinants of financial and law sanction.